2018
DOI: 10.1136/sextrans-2017-053484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rectal douching/enema on rectal gonorrhoea and chlamydia among a cohort of men who have sex with men on HIV pre-exposure prophylaxis

Abstract: Rectal hygiene with RD is a common practice (66%) among HIV-uninfected MSM on PrEP in this study, which increases the odds of acquiring rectal NG and/or CT independent of sexual risk behaviour, substance use and other factors. This suggests interventional approaches targeting rectal hygiene products and practices could reduce sexually transmitted infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(38 reference statements)
0
17
0
1
Order By: Relevance
“…5,9 Common MSM rectal hygiene practices (douching/enemas) can affect microbiome composition in some people [11][12][13] and have been associated with increased infection by HIV and other STIs in MSM. 14,15 Additionally, repeat use of hyperosmotic lubricants significantly decreased Bacteroides and trended toward increasing Prevotella, which could contribute to microbiome shifts. 16 A further, little understood, factor that may influence the microbiome in MSM is the degree to which MSM-associated microbes are spread through intimate contact.…”
Section: Msm-associated Microbes Of Interestmentioning
confidence: 99%
“…5,9 Common MSM rectal hygiene practices (douching/enemas) can affect microbiome composition in some people [11][12][13] and have been associated with increased infection by HIV and other STIs in MSM. 14,15 Additionally, repeat use of hyperosmotic lubricants significantly decreased Bacteroides and trended toward increasing Prevotella, which could contribute to microbiome shifts. 16 A further, little understood, factor that may influence the microbiome in MSM is the degree to which MSM-associated microbes are spread through intimate contact.…”
Section: Msm-associated Microbes Of Interestmentioning
confidence: 99%
“…These gures suggest that RD might be a common practice among MSM in urban China whatever their economic level. The prevalence of RD behavior among MSM in China is close to that of the USA (66%), Kenya (63%) [12,13], the UK, Brazil, and France (53.4-54.3%) [11,14,15], but higher than that in Peru (18.2-27.0%) [28,29] and the Netherlands (13.6-46%) [30,31]. Despite this high prevalence among MSM worldwide, scienti c data for and knowledge of RD in the Chinese MSM population is still insu cient.…”
Section: Discussionmentioning
confidence: 85%
“…This behavior is common among MSM globally, both before and after anal sex. In the previous studies, around 66% and 63% of MSM in the USA and Kenya, respectively, were found to have conducted RD [12,13]. The percentages of MSM employing RD hover around 53.4-54.0% in the UK, Brazil, and France [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, RD is commonly and routinely used globally by MSM in preparation for anal sex. In two studies, around 66% and 63% of MSM in the USA and Kenya, respectively, were found to have conducted RD [5,6]. The percentages of MSM employing RD hover around 53.4-54.0% in the UK, Brazil, and France [4,7,8].…”
Section: Introductionmentioning
confidence: 99%